Geochemistry of the Bagnold dune field as observed by ChemCam and comparison with other aeolian deposits at Gale Crater. Issue 10 (23rd October 2017) - Cousin, Agnes; Dehouck, Erwin; Meslin, Pierre‐Yves; Forni, Olivier; Williams, Amy J.; Stein, Nathan; Gasnault, Olivier; Bridges, Nathan; Ehlmann, Bethany; Schröder, Susanne; Payré, Valérie; Rapin, William; et al.
Abstract: The Curiosity rover conducted the first field investigation of an active extraterrestrial dune. This study of the Bagnold dunes focuses on the ChemCam chemical results and also presents findings on the grain size distributions based on the ChemCam Remote Micro‐Imager and Mars Hand Lens Imager images. These active dunes are composed of grains that are mostly <250 μm. Their composition is overall similar to that of the aeolian deposits analyzed all along the traverse ("Aeolis Palus soils"). Nevertheless, the dunes contain less volatiles (Cl, H, and S) than the Aeolis Palus soils, which appear to be due to a lower content of volatile‐rich fine‐grained particles (<100 μm) or a lower content of volatile‐rich amorphous component, possibly as a result of (1) a lower level of chemical alteration, (2) the removal of an alteration rind at the surface of the grains during transport, (3) a lower degree of interaction with volcanic gases/aerosols, or (4) physical sorting that removed the smallest and most altered grains. Analyses of the >150 μm grain‐size dump piles have shown that coarser grains (150–250 μm) are enriched in the mafic elements Fe and Mn, suggesting a larger content in olivine compared to smaller grains (<150 μm) of the Bagnold dunes. Moreover, the chemistry of soils analyzed in the vicinity of the dunes indicates that they are similar to the dune material. All these observations suggest that the olivine content determined by X‐ray diffraction of the <150 μm grain‐size sample should be considered as a lower limit for the Bagnold dunes. Key Points: Bagnold Dunes Campaign corresponds to the first in situ characterization of active dune field Bagnold dunes lack <100 μm and > 1mm grains Bagnold dunes are overall similar to Aeolis Palus soils in composition but are depleted in volatile‐rich amorphous component and present slightly more olivine Plain Language Summary: The Curiosity rover, which is exploring the Gale Crater on Mars, has been investigating a dune field. This is the first time an active and extensive dune field is explored by a rover on Mars, and therefore, Curiosity used all the instruments on board in order to better understand how the dunes can form and with what processes and also to assess their chemistry. This in situ investigation was a great opportunity to compare with orbital data. Our work is focusing on chemical data from the ChemCam instrument, as well as on grain size distributions from the image analyses of two cameras. We show that, overall, the dunes are similar in chemistry to the soils analyzed along the traverse, but they are depleted in H, Cl, and S, suggesting that they contain less fine‐grained particles or less amorphous component (which is known to be enriched in such elements). This could be due to several processes that we try to investigate. Also, we show that the coarser grains of the dunes (150–250 µm) are enriched in Fe and Mn, probably due to an enrichment in olivine.